The Hamstring Flexibility and Balance Impact on T Kick Speed in Pencak Silat Athletes in Madiun City: A Cross-Sectional Study - Prasetyo, Arsya Hayyu; Kinandana, Gede Parta; Indrayani, Agung Wiwiek; Negara, Anak Agung Gede Angga Puspa (Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction: Pencak silat is a traditional Indonesian martial art that has been an integral part of Indonesian culture for centuries. Among its various techniques, the T kick is known for its higher effectiveness compared to other kicks. To achieve a fast T kick, biomotor components such as flexibility and balance are essential. Methods: This observational analytic study employed a cross-sectional design. Subjects were selected through purposive sampling, consisting of male pencak silat athletes aged 15-18 years, with a total sample size of 116. The study included three variables: two independent variables (hamstring flexibility and balance) and one dependent variable (T kick speed). Data collection involved measuring hamstring flexibility, balance tests, and kick speed tests. The data were analyzed using the Spearman’s rho correlation test. The aim of this study was to determine the relationship between hamstring flexibility and balance with T kick speed in pencak silat athletes in Madiun City. Results: The non-parametric Spearman’s rho analysis showed a significant relationship between hamstring flexibility and T kick speed, with p=0.000 (p<0.05) and a correlation coefficient of 0.348. Additionally, a significant relationship was found between balance and T kick speed, with p=0.000 (p<0.05) and a correlation coefficient of 0.508. Conclusion: Based on these findings, it can be concluded that there is a relationship between hamstring flexibility and balance with T kick speed in pencak silat athletes in Madiun City.   Keywords: Hamstring Flexibility, Balance, Speed, Pencak Silat, T Kick, Madiun City